2017
DOI: 10.1155/2017/2608349
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Surface Expression of HLA-DR, TLR2, TLR4, and TLR9 in Ex Vivo-In Vitro Stimulated Monocytes from Severely Injured Trauma Patients

Abstract: Objective. Trauma patients (TP) frequently develop an imbalanced immune response that often causes infectious postinjury complications. Monocytes show a diminished capability of both producing proinflammatory cytokines and antigen presentation after trauma. TLR2, TLR4, and TLR9 recognize pathogens and subsequently activate monocytes. While there are conflictive data about TLR2 and TLR4 expression after trauma, no studies about the expression of TLR2, TLR4, TLR9, and HLA-DR on monocytes from TP after their seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…(2017) reported different results for the circulating levels of monocytes, while a constant depression of MHC-II expression as well as an impaired production of IL-1β over the time course of ten days after trauma compared to healthy volunteers was observed. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2017) reported different results for the circulating levels of monocytes, while a constant depression of MHC-II expression as well as an impaired production of IL-1β over the time course of ten days after trauma compared to healthy volunteers was observed. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Other studies have shown an impaired expression of TLR2 in trauma patients during the first 48 hours or over a time course of 10 days after trauma compared to healthy volunteers. [ 10 , 24 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that the ex vivo ability of these trauma patients to generate an immune response to lipopolysaccharide stimulation was impaired when compared with healthy volunteers 34. Also, trauma patients have lower expressions of monocyte toll-like receptors compared to healthy volunteers 35. Furthermore, underlining these results, a study performed in 166 polytrauma patients revealed a similar pattern of early IL-10 release and a decrease in human leukocyte antigen—DR isotype expression, potentially reducing macrophage functions 36.…”
Section: Discussionmentioning
confidence: 83%
“…We speculate that TLR2 and TLR4 have the same signal (MyD88-dependent) pathway in new-onset atrial fibrillation patients after acute myocardial infarction. 28,29) As past studies have indicated, new-onset AF after MI is most dependent on infarction size, and AF also could cause harmful cardiovascular events and high mortality. A blood sample is collected before reperfusion therapy and patients only received aspirin, plavix, and statins.…”
Section: Discussionmentioning
confidence: 99%